2022
DOI: 10.1093/ije/dyac192
|View full text |Cite|
|
Sign up to set email alerts
|

Sex differences in childhood cancer risk among children with major birth defects: a Nordic population-based nested case-control study

Abstract: Background Childhood cancer is more common among children with birth defects, suggesting a common aetiology. Whether this association differs by sex is unclear. Methods We performed a population-based nested case-control study using nationwide health registries in four Nordic countries. We included 21 898 cancer cases (0–19 years) and 218 980 matched population controls, born 1967–2014. Associations between childhood cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(42 reference statements)
0
1
0
1
Order By: Relevance
“…The cancer risk associated with having a sibling with birth defects in our study was lower than that of having one’s own birth defect observed in the same source population previously (children: OR = 1.1 versus 1.9, adults: OR = 1.0 versus 1.2). 3 , 6 Having any major birth defect of one’s own was associated with an increased risk of several specific cancers, 3 , 6 but having a sibling with any birth defect was only associated with an increased risk of lymphoid and haematopoietic malignancies (with similar effect estimates: own birth defect: OR = 1.2, 3 sibling with birth defects: OR = 1.16). For childhood cancer, we observed increased risk in three combinations of birth defects and cancers that were present for both own and sibling’s birth defects: (i) nervous system defects and any childhood cancer (own: OR = 6.1 3 , sibling’s: OR = 1.4); (ii) urinary system defects and germ cell tumours (own: OR = 3.9 3 , sibling’s: OR = 2.8); and (iii) limb defects and neuroblastoma (own: OR = 2.5, 3 sibling’s: OR = 2.0).…”
Section: Discussionmentioning
confidence: 91%
“…The cancer risk associated with having a sibling with birth defects in our study was lower than that of having one’s own birth defect observed in the same source population previously (children: OR = 1.1 versus 1.9, adults: OR = 1.0 versus 1.2). 3 , 6 Having any major birth defect of one’s own was associated with an increased risk of several specific cancers, 3 , 6 but having a sibling with any birth defect was only associated with an increased risk of lymphoid and haematopoietic malignancies (with similar effect estimates: own birth defect: OR = 1.2, 3 sibling with birth defects: OR = 1.16). For childhood cancer, we observed increased risk in three combinations of birth defects and cancers that were present for both own and sibling’s birth defects: (i) nervous system defects and any childhood cancer (own: OR = 6.1 3 , sibling’s: OR = 1.4); (ii) urinary system defects and germ cell tumours (own: OR = 3.9 3 , sibling’s: OR = 2.8); and (iii) limb defects and neuroblastoma (own: OR = 2.5, 3 sibling’s: OR = 2.0).…”
Section: Discussionmentioning
confidence: 91%
“…Исследования воздействия пестицидов в жилых помещениях, как правило, основывались на самоотчетах, которые подвержены предвзятости отзывов, что может привести к завышению оценок риска. В некоторых недавних исследованиях использовалась близость жилых помещений к местам применения пестицидов [15]. Данный подход менее подвержен предвзятости, но все еще подвержен ошибкам измерений, которые могут ослабить оценки риска.…”
Section: результаты исследования и их обсуждениеunclassified
“…Spina bifida is a series of malfunctions of neural tube formation and human structure. This defect is more common in girls than boys by birth (Daltveit, 2023) This condition presents both in developed and developing countries as well as urban and rural areas (Aruleba & Jere, 2022). All congenital anomalies about neural tube closure which occur during the first three weeks of embryogenesis include neural tube defects, spina bifida, and anencephaly are severe forms of neural tube defects (Ten et al,2022).…”
Section: Literature Reviewmentioning
confidence: 99%